2021
DOI: 10.1155/2021/2918410
|View full text |Cite
|
Sign up to set email alerts
|

Which Agroforestry Practice Is Beneficial? A Comparative Assessment of the Traditional and the Improved Agroforestry Techniques in the Midhills of Nepal

Abstract: Farmers are predominantly adopting two forms of agroforestry, traditional and improved practices, in the midhills of Nepal, but their efficacy on a comparative basis is poorly assessed, so farmers often confuse whether to continue the traditional practice or embrace the improved practice. We carried out a study in six villages of three districts, interviewed 210 farmers adopting each practice, organized six focus group discussions, and interacted with 24 key informants to compare agroforestry practices from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Traditional (home garden, fodder trees with agricultural crops) and the improved (commercial fruit orchards, coffee plantation, and fodder trees with agriculture crops) practices are existing agroforestry practices in the study sites ( Paudel et al., 2019 , 2021 ). Although two thoughts persist in the region, namely, continue the traditional practice or initiate improved agroforestry practices, farmers were also continuing the traditional practice for basic requirements ( Regmi 2003 ; Kiptot and Franzel 2012 ; Paudel et al., 2019 , 2021 ). However, some farmers were modifying their traditional practice into improved practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional (home garden, fodder trees with agricultural crops) and the improved (commercial fruit orchards, coffee plantation, and fodder trees with agriculture crops) practices are existing agroforestry practices in the study sites ( Paudel et al., 2019 , 2021 ). Although two thoughts persist in the region, namely, continue the traditional practice or initiate improved agroforestry practices, farmers were also continuing the traditional practice for basic requirements ( Regmi 2003 ; Kiptot and Franzel 2012 ; Paudel et al., 2019 , 2021 ). However, some farmers were modifying their traditional practice into improved practices.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change also negatively affects the yield and growth of crops and agroforestry species ( Fischer et al., 2002 ; Agwu et al., 2018 ), so farmers adopt different forms of agroforestry practices ( Paudel et al., 2021 ). Over the past few decades, some farmers have been modifying traditional agroforestry practices to optimize benefits, however, some farmers are continuing traditional ones ( Paudel et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These problems can be overcome by following recommended management practices such as conservation tillage, cover and nurse cropping, crop rotation, integrating climate resilient trees and crops with livestock, efficient cropping and irrigation practices, mulching, proper use of resources and sensible use of off-farm inputs [50]. Some studies compared the adaptation and benefits of these two forms of AF practices [50,51]. Studies reported nearly threefold increase in annual income and diverse benefits from improved AF practices as compared to traditional AF practices [51].…”
Section: Amalgamation Of Traditional and Improved Af Practices To Enh...mentioning
confidence: 99%
“…Some studies compared the adaptation and benefits of these two forms of AF practices [50,51]. Studies reported nearly threefold increase in annual income and diverse benefits from improved AF practices as compared to traditional AF practices [51].…”
Section: Amalgamation Of Traditional and Improved Af Practices To Enh...mentioning
confidence: 99%
“…Farmers in Nepal have been using their experiences to grow trees combined with crops and livestock for centuries (Paudel et al, 2021). Agroforestry practices in Nepal can be classified as (i) farm-based, which include home gardens and trees grown on agricultural fields, and (ii) forest-based, which includes agricultural activities linked to forests (Khadka et al, 2021).…”
Section: Introductionmentioning
confidence: 99%